2000
DOI: 10.1016/s1525-1578(10)60625-3
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Multitarget, Multicolor Fluorescence in Situ Hybridization Assay for the Detection of Urothelial Carcinoma in Urine

Abstract: The purpose of this study was to develop a multitarget, multicolor fluorescence in situ hybridization (FISH) assay for the detection of urothelial carcinoma (UC) in urine specimens. Urinary cells obtained from voided urine specimens of 21 patients with UC and 9 normal donors were analyzed with nine different centromere enumeration probes and a single locus-specific indicator probe to determine an optimal set of FISH probes for UC detection. The four probes with the greatest sensitivity for UC detection were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
175
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(183 citation statements)
references
References 32 publications
(41 reference statements)
2
175
2
Order By: Relevance
“…This UroVysion probe mixture consists of centromeric enumeration probes (CEPs) for chromosomes 3, 7, and 17, and a locus-specific indicator (LSI) probe to the 9p21 band that are labeled with red, green, aqua, and gold fluorophores, respectively [12,13]. The UroVysion™ FISH assay has been increasingly used as a valuable adjunct in detecting and monitoring bladder cancer, not only in cytologically negative, but also in cytologically inconclusive urine samples [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This UroVysion probe mixture consists of centromeric enumeration probes (CEPs) for chromosomes 3, 7, and 17, and a locus-specific indicator (LSI) probe to the 9p21 band that are labeled with red, green, aqua, and gold fluorophores, respectively [12,13]. The UroVysion™ FISH assay has been increasingly used as a valuable adjunct in detecting and monitoring bladder cancer, not only in cytologically negative, but also in cytologically inconclusive urine samples [5].…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of probes have been investigated to determine which combination yields the highest sensitivity and specificity for TCC detection, the optimal combination was found to combine CEPs for chromosomes 3, 7, and 17, with a LSI probe to the 9p21 band. This combination significantly increased both the sensitivity and specificity of the assay compared with single probe analysis [5,6,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The scoring approach used in this study is analogous to that previously developed and validated for the detection of exfoliated malignant transitional cells in urine cytology specimens by multicolor FISH. 23,24 Using this approach, 25 cells are assessed initially focusing on the atypical/metaplastic cells marked by the cytologist in conjunction with their DAPI staining pattern (large, pale, and/or nonhomogeneous staining is typical for dysplastic/carcinoma cells, elongated nuclei with homogeneous DAPI staining are the usual appearance of metaplastic columnar cells). In cases where less than the diagnostic number of cells with FISH abnormalities were identified among the initial 25 cells, additional cells were analyzed and, unless sufficient cells to establish a positive FISH diagnosis were found, all cells on the entire slide were analyzed to ensure that no abnormal population was missed.…”
Section: Fishmentioning
confidence: 99%
“…However, this was later extended to include its use as a screening tool in patients with hematuria and risk factors for urothelial carcinoma. 17,18 Urovysiont FISH has a reported sensitivity of 73-92%, a specificity of 89-96% for urothelial carcinoma detection and several studies have confirmed its usefulness in the diagnosis and surveillance of these tumors. 8,14,[19][20][21][22] The test is designed to detect aneuploidy for chromosomes 3, 7, 17, and loss of the 9p21 locus in malignant urothelial cells that are shed in the urine of persons with urothelial carcinoma.…”
mentioning
confidence: 99%